Design and Implementation of E-Lazisnu in Zakat, Infaq, and Sedekah Mangement With Android Based - Nadia Roosmalita Sari; Annas Ribab Sibilana (Inspiration)
The amil zakat agency is a zakat management institution whose job is to receive and distribute zakat, infaq, and alms to people in need. In several sub-districts in Blitar Regency, the zakat, infaq, and alms management systems, in this case financial recording, financial reporting, and all matters relating to the entry and exit of money are still carried out using a paper-based recording system. Storing data in the form of reports printed on paper is considered insecure, because it could be that the accumulation of reports from year to year will cause the data to become obsolete and even disappear. This study proposes a financial management information system as a financial management medium. The purpose of this research is to develop an Android-based financial management information system as an alternative financial management medium for LAZISNU managers and to determine product feasibility. The research and development methodology used in this research is Research and Development (R&D). This methodology covers all matters related to development to produce quality software. Based on the trials, the results obtained were 82.5 % from software experts, 90.5 % from material experts, and 86.5 % from user field tests. Based on these results, an Android-based financial management information system is feasible to use as a financial management medium with an average validation value of 86.5 %.